Smart specialization strategies as booster of regional entrepreneurial and innovative ecosystems - Lopes, João Nuno Morais (2019)
The general objective of this thesis is to “analyse the relationship between innovation, entrepreneurship and competitiveness in the context of Research and Innovation Smart Specialisation Strategies (RIS3)”, following the quadruple helix network approach to regional economies in economic and social development. In order to reach the proposed objective, a typology of mixed research, presented in Chapters 2 to 5, was used. In Chapter 2, two studies were carried out. The first study seeks, through a bibliometric analysis, to ascertain the developments that occur in the RIS3 studies to identify gaps and opportunities for future research. This bibliometric review was based on the SCOPUS database with the selected sample containing all the articles with the keywords “Research and Innovation Strategies for Smart Specialisation” or “RIS3”. Our findings detail six clusters in RIS3 research, which help to contextualise literature review: 1) business discovery; 2) smart specialisation; 3) innovation; 4) specialisation; 5) regional policies; and 6) regional development. This study also establishes perspectives for future lines of research and, correspondingly, seeks to convey a broad theoretical basis that can serve as a starting point for future studies. In the second study in Chapter 2, a bibliometric analysis of academic entrepreneurship was sought. We carried out extensive research (1971 - 2017) in the Web of Science database that allowed us to identify seven clusters in the literature: 1) entrepreneurial universities; 2) university-industry interactions; 3) university-industry knowledge transfers; 4) university-industry innovation networks; 5) university entrepreneurship; 6) university-industry industrial property; and 7) innovation ecosystems. This study reinforces the coherence and scientific structure of the existing literature and serves as a starting point for future studies in this field. In Chapter 3, the study sought to identify the variables which best explain the performance of innovative regions in Europe by implementing regional strategies for smart specialisation. We followed a quantitative methodology and applied linear regression as a method. To conduct this study, we collected data from the Regional Innovation Scoreboard. The results led to an explanatory model of invocation of performance for the moderate innovator regions. It also identifies some possible measures and suggestions to help decision-makers improve the innovation performance of these regions. In Chapter 4, the study aimed to evaluate stakeholder perceptions regarding the adequacy of the smart specialisation strategies defined for their regions in RIS3. We adopted a quantitative methodology through questionnaires to the different stakeholders in the Portuguese regions, according to the VRIO model applied to the regions. The results of the study emphasise that stakeholder perceptions about the adequacy of defined smart specialisation strategies for their regions do not match the smart specialisation strategies defined by their policy makers in RIS3. This study attempts to contribute to an innovative framework that helps policy makers assess and measure regional performance. The study also proposes measures to bridge the gaps found in regional strategies for smart specialisation. Chapter 5 deals with two studies. The first study sought to analyse the dynamics underlying the mechanisms of transfer and commercialisation of university technology. We adopted a qualitative research methodology, which incorporates different case studies, interviews and applied research of the actors involved in universities, business incubators and startups. This work highlights the mechanisms of technology transfer and marketing support, including the identification of the difficulties and opportunities present in the context of cooperation networks. By examining the incubators in operation and the managers of incubated companies together with the analysis of cooperative research, development and innovation projects backed by European funding, we were able to gain insight into the different technology transfer and marketing processes. Falling within the framework of the third mission of universities, this study demonstrates not only the importance of cooperation networks in research, development and innovation, but also how the consequent commercialisation of new products and services has positive consequences for economic growth. In the second study in Chapter 5, resources and capacities were evaluated in island regions, and it was also intended to understand how value creation and commercialisation are carried out in existing ecosystems. A qualitative research methodology was followed through a case study, incorporating interviews with incubators managers from the island regions of Portugal (Azores and Madeira). The results show some difficulties as a result of the insularity of ecosystems. To shorten the asymmetry of island regions compared to other non-island regions, a new model is proposed to help these regions overcome their socio-economic problems. Finally, in order to couple all the findings achieved in chapters 2 to 5, the Regional Helix Assessment Model was presented, clarifying the role of the different actors in the quadruple helix context and their potential contribution to increasing regional competitiveness.